Implementación de una máquina limpiadora y clasificadora de tuna para reducir el tiempo de empacado. - León Chiluisa, Jonathan Stalin (2022)
The objective of this degree project is the implementation of a prickly pear cleaning and sorting machine for the cultivation of Mr. Leon Hermenegildo Malliquinga Bustos in the province of Cotopaxi Canton Salcedo parish Panzaleo neighborhood San Jose de Jacho, with the implementation of the machine mentioned above we will reduce the time spent on packing that fruit. The process of cleaning and classification of the prickly pear is investigated, where the time spent in those activities is analyzed, starting with the amount of fruit to be packed, the average value of the size of the prickly pears that are in a bucket was determined and thus the structural dimensioning is developed, the distance of the rollers and the mechanism that will be able to remove and classify the fruit. To determine the number of rollers, the volume of fruit grown for cleaning and sorting was analyzed, the analysis of the strength of the rollers and the sizing of the chain is proportional to the cleaning quality of the product, since the more rollers there are, the better the cleaning of the fruit. Once the proposal was implemented, field tests were carried out to determine the correct operation of the machine and thus determine the time used in the cleaning and sorting process, resulting in two and a half minutes. It was concluded that the time used manually for the cleaning and classification per bucket is 7 min, while with the implementation of the prototype cleaner and classifier of prickly pears was reduced to a time of 2 min and 30 sec per bucket and also its capacity is from 2 to 3 buckets.